Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2022
DOI: 10.1186/s43042-022-00230-y
|View full text |Cite
|
Sign up to set email alerts
|

The correlation between P53 and COX-2 expression and the pathological alteration in hepatocellular carcinoma

Abstract: Background Hepatocellular carcinoma (HCC) is among the highest life-threatening malignancies. On both a molecular and histological level, HCC is a highly heterogeneous malignancy. This study was aimed to study the correlation between the molecular expression of some molecular biomarkers (P53 and Cox-2) and the histopathological alterations in the chemically induced HCC by Diethylnitrosamine (DEN) in Adult female Rats. The liver tumor induction was done by injection of DEN intraperitoneally one,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
0
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 47 publications
0
0
0
Order By: Relevance
“…The present results aligned with earlier findings revealed the downregulation of p53 expression in HCC [67]. The absence of an effective form of p53 is essential for the induction of growth and proliferation of tumor cells in most types of cancers, including HCC [68].…”
Section: Discussionsupporting
confidence: 93%
“…The present results aligned with earlier findings revealed the downregulation of p53 expression in HCC [67]. The absence of an effective form of p53 is essential for the induction of growth and proliferation of tumor cells in most types of cancers, including HCC [68].…”
Section: Discussionsupporting
confidence: 93%
“…Studies have shown that this gene is mutated in 69-24% of HCC cases (Osada et al, 2004). An experimental study in adult female rats showed that there is a significant relationship between P53 gene expression and HCC so that HCC staging is obtained by detecting the expression of p53, which is a molecular marker (Sakr et al, 2022). Yang et al (2022) in a study with sequence of bioinformatics analysis identified novel characteristics in TP53-mutant HCC and provided new insights into a precise individualized therapy for HCC.…”
Section: Discussionmentioning
confidence: 99%